2019
DOI: 10.1016/j.aott.2019.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and evaluation of bone and soft tissue tumors operated in a tertiary care center

Abstract: Objective The aim of this study was to retrospectively evaluate the patients who were operated in our orthopedics and traumatology clinic with the suspection of bone and soft tissue tumors. Methods A total of 3133 patients (1146 (46.5%) female and 1318 (53.5%) male) who presented to our tertiary clinic from different regions of Turkey between January 2002 and July 2013 with the presumed diagnosis of bone and soft tissue tumors were analyzed according to age, gender, bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 7 publications
6
34
0
2
Order By: Relevance
“…Considering the prevalence of tumors, the most common benign soft tissue tumors were reported as lipoma, ganglion and giant cell tumor of tendon sheath, respectively, which was consistent with the literature (6)(7)(8). Whereas, the most common malignant soft tissue tumors have been reported as liposarcoma, pleomorphic cell sarcomas (malign fibrous histiocytomas), leiomyosarcomas, and synovial sarcomas, respectively, in a large referral population (6,10).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Considering the prevalence of tumors, the most common benign soft tissue tumors were reported as lipoma, ganglion and giant cell tumor of tendon sheath, respectively, which was consistent with the literature (6)(7)(8). Whereas, the most common malignant soft tissue tumors have been reported as liposarcoma, pleomorphic cell sarcomas (malign fibrous histiocytomas), leiomyosarcomas, and synovial sarcomas, respectively, in a large referral population (6,10).…”
Section: Discussionsupporting
confidence: 85%
“…Regarding sex, male dominancy has been reported with a ratio of 1.5 for musculoskeletal tumors by Solooki et al's (13), whereas Solakoglu and Benzer (19) reported a male dominancy in bone tumors and female dominancy in soft tissue tumors which was supported by Ozturk et al (8). In the current study, musculoskeletal tumors have been found more common in males than females which could be contributed to the study population of male domination.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Patolojik kırık, büyük bir komplikasyondur ve litik iskelet lezyonları ile daha sık ilişkilidir. [11,12] Kemiğe metastaz yapabilen diğer tümörler arasında; melanom, nöroblastom, hepatosellüler karsinoma, karsinoid tümörler ve paraganglioma ile bazı solid tümörler bulunur, bu tür metastazların görülme sıklığı daha azdır.…”
Section: Kemi̇ğe Nadi̇r Metastaz Yapan Tümörler Ve öZelli̇kleri̇unclassified